2020
DOI: 10.1016/j.ebr.2020.100380
|View full text |Cite|
|
Sign up to set email alerts
|

Ketogenic diet in Zambia: Managing drug-resistant epilepsy in a low and middle income country

Abstract: Globally, drug-resistant epilepsy affects one third of people living with epilepsy. With limitations in treatment options for refractory epilepsy in resource-limited regions, ketogenic diet therapy is an important option to consider. Utilizing the 2015 International League Against Epilepsy recommended minimum requirements for ketogenic diet therapy, three male children with refractory epilepsy, aged 2.5, 6.5 and 10 years, were initiated on the classical ketogenic diet using locally available food in August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, the rapid antifungal effect of KD after only several days has implications for a clinical setting, in which a dietary intervention can be introduced during an established infection. For instance, several studies have found that a KD is a feasible treatment intervention for pediatric epilepsy in LMICs, and success is increased when administered in hospital settings ( 43 46 ). Furthermore, a KD was found to significantly alter the human immune system, microbiome, and metabolome after just 2 weeks of therapy ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rapid antifungal effect of KD after only several days has implications for a clinical setting, in which a dietary intervention can be introduced during an established infection. For instance, several studies have found that a KD is a feasible treatment intervention for pediatric epilepsy in LMICs, and success is increased when administered in hospital settings ( 43 46 ). Furthermore, a KD was found to significantly alter the human immune system, microbiome, and metabolome after just 2 weeks of therapy ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study in Canada [13] evidenced that PWE, who initiated KDT, experienced decreased emergency department visits and inpatient visits, and healthcare costs. Additionally, KDT is becoming a rising trend in resource-limited countries, with successful experiences in Egypt [14] and Zambia [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet, which consists of a low carbohydrate, high fat, and moderate protein intake, is a popular therapeutic choice for drug-resistant epilepsy in children and is used extensively in the majority of specialized paediatric epileptic centres worldwide 21 . This type of diet has shown promising results in research done in Zambia among paediatric drug-resistant epileptic patients 22 . Because of cost, a shortage of neurosurgeons, and a lack of infrastructure to support advanced technologies, most of sub-Saharan Africa does not have access to epilepsy surgery such as resection surgery, deep brain stimulation, corpus callosotomy, hemispherectomy, or other less invasive techniques 23 .…”
Section: Risk Factors Diagnosis and Management Of Epilepsy In Africamentioning
confidence: 99%